Sensing Informal Networks in Organizations. (April 2015) - Orbach, Maya; Demko, Maegen; Doyle, Jeremy; Waber, Benjamin N.; Pentland, Alex (Sandy)
We present an examination of informal network structure within the sales division of a global manufacturing organization. Sociometric Badges were used to collect data on face-to-face interactions over a total of 8 weeks, the latter half of which was spent in a redesigned workspace. These data were supplemented by employees' e-mail and instant messaging log activity. The allocation of an individual's communication among colleagues reflected the company's structure as a post-bureaucratic organization. The observed interteam communication patterns differed from those expected to arise based on the various functions performed by each team throughout the sales cycle, suggesting that the communication needs of each team were not wholly provided for by the available media. A subset of workers who were encouraged to utilize flexible seating arrangements in a remodeled space had a higher proportion of face-to-face interactions with colleagues outside of their team, while employees seated far away from each other were less likely to exchange e-mail. This research has implications for companies hoping to understand the structure of informal networks within their organization as well as those considering workplace redesign as a method of stimulating communication within these networks.